Assessment of healthcare providers’ knowledge, attitude, and practice toward medical research in southwest Saudi Arabia: a cross-sectional study - Hadi Al Sulayyim; Ali Alrashah; Ali Al Mansour; Fahad Al Sleem; Yahya Alfaifi; Mansour Alyami; Ali Alkhudeer; Hassan Al Hutaylah; Yousef Allajam; Abdullah Alkhurais; Noura Alfaifi; Mansour Majrshi; et al. (BMC Medical Education)
Abstract Background Medical research plays a crucial role in advancing the treatment and prevention of diseases, in addition to enhancing public health. Objectives This study aims to assess knowledge, attitude, and practice (KAP) of healthcare providers (HCPs) in relation to medical research, identify motivating factors and barriers that prevent them from conducting research, and identify associated factors with good knowledge, practice and positive attitude. Methods In this cross-sectional study, a validated questionnaire was employed to gather data of HCPs who work at healthcare institutions affiliated with MOH. The Proportionate stratified random sampling method was used to recruit HCPS. Proportion (%), and median and interquartile range (IQR) were used to represent the data. Logistic regression analysis was carried out to identify associated factors with good knowledge, positive attitude, and good practice. Results A total of 285 HCPs were included in the analysis. The median score for knowledge was 43%, with scores ranging from 14 to 57%, for most participants showing variability in their knowledge levels. For attitude, the median score was 100%, indicating a generally positive outlook, with scores between 80% and 100% for most participants. The practice score had a median of 59%, with scores ranging from 33 to 83%, showing a wide range in research activity among the HCPS. The most reported motivators were strength of the resume (91.80%) and fulfilment of work requirements (90.80%). The most reported barriers were lack of financial support (82.3%), poor time management (78.7%), no enough research facilities (75.2%), lack of motivation (74.8%), inadequate skills and knowledge (72.3%), and lack of rewards (71.6%). Good knowledge was significantly associated with taken research methodology course (p. value = 0.001) and qualification (p. values = < 0.05). Positive attitude was significantly associated with workplace and qualification. Nationality (p. value = 0.005) and taking a research methodology course (p. value = 0.001) were significantly associated with good practice. Conclusion Although HCPs showed a positive attitude towards medical research, their knowledge and practice were inadequate. They are necessarily needed for amelioration. This improvement can be achieved through effective and regular research methodology courses, workshops, and enhancement of the research environment.